Facile preparation of carbon nanotube aerogels with controlled hierarchical microstructures and versatile performance. (August 2015) - Dong, Liubing; Yang, Qian; Xu, Chengjun; Li, Yang; Yang, Deming; Hou, Feng; Yin, Hongfeng; Kang, Feiyu
Abstract: Carbon nanotube (CNT) aerogels with controlled hierarchical microstructures and versatile performance were prepared by a freeze-drying method under the facile freezing temperature of −20 °C. The as-prepared CNT aerogels were composed of CNT/binder (sodium carboxymethylcellulose, CMC) hybrid sheet structures, whose morphologies could be controlled by changing the weight ratio of CMC solution to CNT paste. The aerogels displayed a very low density of 32.7–77.7 mg/cm 3, fairly high mechanical strength, good machinability, an outstanding electrical conductivity of 0.034–0.162 S/cm, and an ultralow thermal diffusivity of 2.09–4.54 mm 2 /s. In addition, we proposed formulas to describe the relationships between volume density of the fabricated aerogels and solid content or carbon content in CNT slurries.